Characterisation of gut microbiota in Malaysian cancer patients using V3-V4 region of 16S rRNA gene sequencing - Siti Farah Norasyikeen, Sidi Omar; Yvonne Lim, Ai Lian; Syaza Zafirah, Ab Rahman; Azdayanti, Muslim; Qasim, Ayub; Syafnaz, Amin Nordin; Vesudian Narcisse Mary, Sither Joseph; Sabri, Musa; Timothy Adrian, Jinam; Romano, Ngui (Springer Nature Limited, 2025)
Recent studies suggested a potential connection between gut microbiota changes and cancer onset. However, conflicting results make it challenging to understand the role of gut microbiota dysbiosis in cancer, particularly in underrepresented populations like those in Southeast Asia. To address this gap, we analysed the diversity and composition of gut microbiota in 65 faecal samples, which included 48 from cancer patients with various malignancies and 17 from healthy controls. Patients were categorised into four groups: symptomatic patients undergoing cancer treatment, asymptomatic pre-treatment and during cancer treatment, and healthy controls. Genomic DNA was extracted, and the V3-V4 region of the 16 S rRNA gene was sequenced. Our findings revealed significant differences in the alpha diversity (p ≤ 0.05) between cancer patients and controls. Asymptomatic patients under treatment showed slightly lower alpha diversity than pre-treatment patients, but this difference was not statistically significant (p = 0.06). We identified 13 genera with over 20% difference in abundance between patient groups and controls. Asymptomatic patients receiving treatment and pre-treatment patients exhibited enrichment in Enterococcus, whereas Prevotella, Faecalibacterium, Brevundimonas, and Pseudomonas were significantly reduced compared to controls. Symptomatic patients had higher levels of Enterococcus and Staphylococcus, while Ruminococcus was enriched in asymptomatic patients. These underscore the distinct differences in gut microbiota composition between cancer patients and healthy individuals, particularly in symptomatic cases with potential biomarkers such as Enterococcus, Prevotella, and Faecalibacterium. Our study suggests that cancer treatment may not significantly alter the gut profile of cancer patients. Further research is needed to comprehend the implications of these findings fully.